Corrigendum: Large-scale neuromorphic spiking array processors: a quest to mimic the brain - Thakur, Chetan Singh; Schemmel, Johannes (Frontiers in neuroscience, 2019)
Corrigendum: "Large-scale neuromorphic spiking array processors: a quest to mimic the brain"
Gesehen am 05.07.2019